Calculer puis simplifier si possible tous les résultats suivantes:
A= -9/8+ 15/8=
B=17/12 - 11/3=
C= 3/4 - 4/3=
D= 2+ 5/6 - 7/2=

A= -7/4 * 11/9=
B= 15 * 14/35=
C= 24/(- 35) * (-42)/36=

A= 6/7 / 9/5=
B= 15/8 / (-6)=
C= 12/35 / 8/21=

1

Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-26T16:54:54+01:00
A= -9/8+ 15/8=4/8=1/2
B=17/12 - 11/3=17/12-44/12=-9/4
C= 3/4 - 4/3=9/12-16/12=-7/12
D= 2+ 5/6 - 7/2=24/12+10/12-42/12=-2/3

A= -7/4 * 11/9=-77/36
B= 15 * 14/35=210/35=6
C= 24/(- 35) * (-42)/36=24/35*7/6=4/5

A= 6/7 / 9/5=6/7*5/9=30/63=10/21
B= 15/8 / (-6)==-15/(-48)=-5/16
C= 12/35 / 8/21=
12/35*21/8=9/10
Bonjour les deux A= -9/8+ 15/8=6/8=3/4 A= -7/4*11/9= -77/36=- 11/18